Preparation method of wood particle board capable of being smoothly demoulded
By using polyisocyanate and photobase-producing components in the binder composition of wooden pellet plates and catalyzed by UV light irradiation, the problems of insufficient cold pressing adhesion and poor hot pressing release effect in the prior art are solved. Long-term cold pressing adhesion and efficient mold release effect are achieved, reducing production costs.
Patent Information
- Application Number
- CN202310770783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot provide long-term, sufficient cold pressing adhesion and good mold release effect after hot pressing, resulting in low production efficiency and high cost.
Using a binder composition, including polyisocyanate and photobase-producing components, the reaction of NCO groups on the surface of wooden particle boards is catalyzed by UV light irradiation, thereby improving cold press adhesion and hot press release effect.
The cold pressing adhesiveness after glue is achieved for a long time after applying the glue and the good mold release effect after hot pressing, which reduces production costs, and improves the internal bonding strength and water absorption and expansion resistance of the wooden composite products.
Smart Images

Figure BDA0004307775860000151 
Figure BDA0004307775860000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of artificial boards, and in particular relates to a method for preparing a wood particle board which can be demoulded smoothly. Background Art
[0002] Compared with traditional trialdehyde glue (urea-formaldehyde glue, phenol-formaldehyde glue, melamine-formaldehyde glue), the use of isocyanate as an adhesive for wood composite products has the advantages of no formaldehyde release, fast curing, higher bonding strength, better water resistance, and less deformation. However, there are also some problems in the production process. Since isocyanate is non-sticky at room temperature, it cannot form a molded slab with a certain shaping ability after being applied to wood particle materials, and it is easy to scatter due to vibration after cold pressing; in addition, isocyanate has a strong affinity for metal during hot pressing, resulting in the slab being bonded to the press belt after hot pressing. Therefore, when isocyanate is used as an adhesive for wood composite products, a release agent must be used at the same time. Long-term use of the release agent will contaminate the surface of the press and requires regular manual cleaning, which further increases the cost of raw materials and labor.
[0003] The prior art only focuses on solving the problem of a tackifier composition that can provide cold-pressing adhesion, or providing a demolding agent (internal demolding agent or external demolding agent) or a demolding solution with a demolding effect. For example, patent CN103118866A discloses an adhesive system containing acrylic or styrene-butadiene polymer as a tackifier. The adhesive system can be used for orienting wood unit materials in the preparation of particleboard or fiberboard, improving the production efficiency of wood composite products and the mechanical properties of composite products; patent CN102165015A discloses a processing aid reactive to isocyanate and containing a continuous phase and a discontinuous phase. The additive is a grafted polyol, which can improve the water resistance and swelling resistance of wood composite products and provide the cold-pressing adhesion required in the preparation process. Patent CN105602467B discloses a release agent for use as an isocyanate adhesive. The release agent is compounded from ingredients such as sodium tripolyphosphate, peregal O and sodium dodecylbenzene sulfonate. The release agent has a simple preparation process, good emulsification stability and excellent demoulding performance.
[0004] The viscosity enhancement solution provided in the above patent has the problem of weak viscosity in actual application. The slab formed after cold pressing is not strong and easy to disperse, and the effective time of the adhesion of the wood particle mixture is short. If there is a sudden stop during production, the viscosity of the wood particle mixture after sizing will gradually weaken after being stored for more than 10 minutes, which undoubtedly brings certain risks to the continuous production line. In order to avoid the cumbersome production process caused by multiple additives and various additional costs, the effective time of the adhesion of the wood particle mixture after sizing is extended.
[0005] In summary, the adhesive compositions of the prior art cannot provide long-term and sufficient cold-pressing adhesion after gluing, and in particular cannot provide good demoulding effect after hot pressing. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a wood particle board which can be demoulded smoothly. The adhesive composition prepared by the method can provide long-term and sufficient cold pressing adhesion after gluing, and can have a good demoulding effect after hot pressing.
[0007] In order to achieve the above invention object, the present invention adopts the following technical solution:
[0008] A method for preparing a wood particle board that can be demoulded smoothly, the method comprising the following steps:
[0009] S1: mixing the binder composition with the wood particle material and paving the mixture into a shape to be pressed, and cold pressing the mixture to obtain a formed slab;
[0010] S2: irradiating the slab surface with UV light;
[0011] S3: hot pressing the slab of S2 to obtain a wood particle board;
[0012] The photobase generating component contained in the adhesive composition described in S1 catalyzes the reaction of NCO groups on the surface of the wood particle board after being irradiated with UV light in S2.
[0013] In the prior art, only cold-pressing adhesion is often focused on, while the effective time of such adhesion is ignored, and a release agent needs to be used in combination, which results in a high comprehensive raw material cost of isocyanate adhesives. The adhesive composition of the present invention not only retains the advantage of isocyanate adhesives that they do not release formaldehyde, but also can provide the cold-pressing adhesion required in the production of wood particle composite products. At the same time, the wet curing reaction of the catalytic surface NCO produced by photobase generation after illumination solves the problem of sticking boards, thereby improving production efficiency. The wood composite product prepared by the adhesive composition of the present invention has good internal bonding strength and water absorption and swelling resistance, which is not involved in the prior art.
[0014] In one embodiment of the present invention, S1 the adhesive composition comprises component A and component B, wherein component A contains polyisocyanate and a photobase generating component, and component B contains an acrylate polymer; preferably, component A accounts for 50-95wt% of the adhesive composition, and component B accounts for 5-50wt% of the adhesive composition; preferably, the photobase generating component accounts for 0.1-5wt% of component A.
[0015] In one embodiment of the present invention, the polyisocyanate in S1 is an aromatic isocyanate, preferably diphenylmethane diisocyanate MDI and / or polymethylene polyphenyl isocyanate PMDI, more preferably PMDI.
[0016] In one embodiment of the present invention, the photobase generating component in S1 is one or more of a carbamate compound, a borate compound, a quaternary ammonium salt compound, and a nitrogen heterocyclic amidine compound, preferably a quaternary ammonium salt compound and / or a borate compound.
[0017] In one embodiment of the present invention, the acrylic ester polymer described in S1 is obtained by polymerizing two or more monomers selected from the group consisting of C2-C14 (meth) alkyl acrylate, (alkyl) styrene, vinyl alkyl benzene, unsaturated carboxylic acid, alkyl vinyl ester, and polyol (dimethyl) diacrylate.
[0018] In one embodiment of the present invention, the acrylate polymer described in S1 contains a photosensitive monomer containing a C=C double bond capped with a coumarin group; preferably, the photosensitive monomer containing a C=C double bond capped with a coumarin group accounts for 0.01-2 wt % of the acrylate polymer.
[0019] In one embodiment of the present invention, the Tg of the acrylic acid ester copolymer described in S1 is -40°C to 20°C, preferably -20°C to 10°C.
[0020] In one embodiment of the present invention, the amount of the binder composition added in S1 is not less than 2% of the total weight of the wood particle material.
[0021] In one embodiment of the present invention, the wavelength of the UV light irradiated on the surface of the slab in S2 is 200-650 nm, preferably 300-400 nm.
[0022] In one embodiment of the present invention, the S2 illumination time is 5-60s.
[0023] Another object of the present invention is to provide a binder composition for preparing wood particle boards.
[0024] A binder composition for preparing a wood particle board, the composition is the binder composition used in the method for preparing the wood particle board.
[0025] The preparation process and composition described in the present invention have the following beneficial effects: 1) after the composition is applied to the wood particle material, the mixture can maintain sufficient adhesion at 0-50°C within 2 hours, ensuring that the cold-pressed slab has a certain shaping and vibration resistance. The cold-pressed adhesion measured immediately after gluing and after storage at 35°C for one hour using the cold-pressed adhesion test method provided by the present invention is not less than 5cm; 2) in the absence of spraying a release agent, the hot-pressed steel plate and the slab can be smoothly demolded without the aid of external force after hot pressing.
[0026] The adhesive composition disclosed in the present invention can, on the one hand, provide the adhesion required for cold pressing of wood particle materials, and at the same time, the effective time of the adhesion can be maintained long enough to cope with different production conditions. On the other hand, the adhesive composition will not stick to the hot-pressed steel belt during hot pressing, and a good demoulding effect can be achieved without the need for additional spraying of a demoulding agent. The wood particle composite product obtained by hot pressing using the adhesive composition has excellent mechanical properties, and can provide excellent mechanical properties of a board that is no less than that of a board with the same amount of PMDI added. From this aspect, a solution for adhesives for wood composite products with lower costs is also provided.
[0027] In a specific embodiment of the present invention, the adhesive composition disclosed in the present invention for preparing wood particle composite products has a very slow reaction speed at room temperature with the isocyanate component and the polyacrylate copolymer component. The NCO conversion rate is less than 30% within 2 hours, and the adhesive composition has good adhesion to the wood particle material in the range of 0°C to 50°C, and the adhesion can be maintained for more than 1 hour. After cold pressing and exposure, the photosensitive groups contained in the polyacrylate copolymer chain are excited, and the photolatent base component in the isocyanate component releases alkaline substances (such as amine substances), which catalyzes the moisture curing of NCO on the surface of the slab, avoiding the reaction between the surface of the slab and the metal steel belt to cause the board to stick. During the hot pressing process, NCO cures quickly, improves the bonding strength between the wood particle materials, and has good mechanical properties and anti-water absorption and expansion properties. In addition, the technical solution provided by the present invention can greatly improve production efficiency, can produce a good demoulding effect after a very short illumination time, and has important practical application value.
[0028] Compared with the adhesive components for wood particle composite products disclosed so far, the adhesive composition disclosed by the present invention has a long effective time of cold pressing adhesiveness, can meet the adhesiveness requirements of most application environments for a long time at temperature, and avoids the risk of the raw materials after gluing being unable to be used due to performance loss after long-term storage due to emergency shutdown; the application process is simplified, and not only can the cold-pressed slab be provided with good cohesion, but also good demoulding effect, thus avoiding the use of demoulding agents and reducing production costs; the adhesive composition has better tolerance to various wood particle materials of different shapes and wood types, and will not have a negative impact on the mechanical properties of PMDI-type wood particle composite products.
[0029] Another object of the present invention is to provide a method for preparing a wood particle board that can be demoulded smoothly.
[0030] The invention discloses a method for preparing a wood particle board which can be demoulded smoothly. The method is the above-mentioned method, and the method is used for preparing artificial boards, and is preferably used for preparing oriented strand boards, oriented laminated timber, and fiberboards.
[0031] The adhesive composition disclosed in the present invention can be applied to particle boards, such as low-density particle boards (LDF), medium-density particle boards (MDF), high-density particle boards (HDF), particle boards (PB), and can also be used for oriented strand boards (OSB), fiberboards, etc. The wood particle composite products described in the present invention can be in the form of other wood composite boards, not limited to those mentioned in this article and in the embodiments.
[0032] Compared with the prior art, the adhesive composition of the present invention has the following beneficial effects:
[0033] The adhesive composition of the present invention not only retains the advantage of no formaldehyde release of isocyanate adhesives, but also can provide the cold pressing adhesion required in the production of wood particle composite products, and at the same time solves the problem of sticking boards through the wet curing reaction of the catalytic surface NCO produced by photobase after illumination, thereby improving production efficiency. The wood composite product prepared by the adhesive composition of the present invention has good internal bonding strength and anti-water absorption and expansion performance. DETAILED DESCRIPTION
[0034] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0035] All raw materials in the present invention can be purchased from the market unless otherwise specified.
[0036] The adhesive composition prepared in the present invention is characterized by the following method, and the test method used includes:
[0037] A) Cold Press Adhesion
[0038] Cold pressing adhesion refers to the adhesion between particles of the mixture after the wood particle material is mixed with the adhesive composition; in the present invention, cold pressing adhesion is expressed by the ability of the slab formed after cold pressing to maintain its original shape. The specific test method is as follows:
[0039] The cold press adhesion test is carried out at room temperature and is evaluated using the "inclined push test method". The specific steps are as follows:
[0040] 1) Weigh 2 kg of wood particles into a glue mixer, start stirring, and then use a spray gun to spray the adhesive composition into the wood particles in the glue mixer;
[0041] 2) After the glue is applied, take about 1.5 grams of wood chips and use a moisture tester to test the moisture content of the wood chips after glue application. If the moisture content is lower than the design range (in this test, the moisture content is uniformly (12±1)%), add water according to the test results; if the moisture content is higher than the design range, repeat steps 1) and 2) until the moisture content is within the design range.
[0042] 3) Weigh 500g of the glued wood particles and place them in a 30*30cm frame, evenly flatten them and squeeze them into shape;
[0043] 3) Cover the formed slab with a steel plate and place it on the press, place an 8mm thick thickness gauge on both sides of the slab, set the pressure of the press to 4.0MPa, and start cold pressing for 20s;
[0044] 4) Remove the cold-pressed slab, place it flat on a 45° wooden slope, and push the slab down the slope at a constant speed within 5 seconds;
[0045] 5) Record the number of slab breaks and the length of the fracture (i.e. the length of the first fracture), and repeat the test twice. The fewer the number of slab fractures and the longer the length of the fracture, the better the cold pressing adhesion.
[0046] 6) Place the glued wood particles at 35°C for 1 hour, repeat the above steps, and record the cold press adhesion test results.
[0047] B) Preparation of wood composite products and evaluation of demoulding effect
[0048] 1) Unless otherwise specified, the content of each component in the present invention is calculated based on the total weight of the absolutely dry wood particle material. Each group of the adhesive composition is applied to the wood particle material; it is evenly paved in a rectangular frame of 30*30cm in length and width, and the paving mass ratio of the surface layer to the core layer is controlled to be 6:4;
[0049] 2) Set the cold pressing pressure to 4.0 MPa for pre-pressing for 20 seconds to form the slab, and expose the formed slab to UV light for a set time; hot press the slab at 220°C and a hot pressing factor of 5 s / mm. The thickness of the slab after hot pressing is controlled to be (18 ± 1) mm, and the density is (650 ± 20) kg / m 3 ;
[0050] Repeat the test 3 times, observe the adhesion of the slab to the steel strip after each hot pressing, and divide it into four situations according to the severity of the sticking situation: complete demoulding, slight sticking, sticking, and severe sticking. If there is no sticking phenomenon, the demoulding effect is good. The earlier the sticking phenomenon occurs and the more serious the sticking situation is, the worse the demoulding effect is.
[0051] C) Mechanical properties of wood particle composite products
[0052] After the hot-pressed board was placed at room temperature for 24 hours, the mechanical properties of the board were evaluated by referring to the test methods for internal bonding strength, static bending strength, elastic modulus and water absorption expansion rate in the national standard GBT 17657-2013.
[0053] In the examples and comparative examples, % refers to mass %.
[0054] The technical solution of the present invention is further illustrated below in conjunction with specific embodiments, but does not constitute any limitation.
[0055] Example 1
[0056] A) Preparation of Adhesive Composition A
[0057] i) Isocyanate component a
[0058] In this embodiment, the isocyanate component is selected from Wanhua Chemical Group CW20 product, CW20 accounts for 85% of the total weight of the adhesive composition, and the photobase generating component selects borate photobase generating component WPBG-345 (purchased from Lumiprobe), and the added amount accounts for 0.2% of the total weight of the isocyanate component.
[0059] ii) Polyacrylate copolymer a
[0060] 40 g of 7-hydroxy-4-methylcoumarin, 12.7 g of KOH and 3 g of polyethylene glycol were dissolved in deionized water at 45°C. After 20 minutes, 32.6 g of p-chloromethylenestyrene was added and the reaction was carried out for 48 hours. The obtained product was dissolved in tetrahydrofuran and then purified by precipitation in a 75% volume fraction methanol aqueous solution to obtain coumarin styrene monomer.
[0061] Weigh 60g of styrene, 110g of butyl acrylate, 10g of acrylic acid, 20g of isooctyl acrylate and 4.5g of homemade coumarin styrene and emulsify them with 30g of 0.5wt% sodium dodecyl sulfate aqueous solution; add 300g of 0.2% NaHCO to the bottom of the reaction flask. 3 solution, add monomer pre-emulsion and 40g of 2.4% Na 2 S 2 O 8 The solution was stirred for 4 hours, and after the dropwise addition was completed, the temperature was raised to 85°C and kept for 0.5 hour, and finally cooled to room temperature for discharge.
[0062] B) Pressed wood particle composite products
[0063] Glue was applied to the surface and core wood particle materials according to the addition amount of each component in the table below. After gluing, boards were made with reference to the preparation method of the aforementioned wood particle composite products. UV light with a wavelength of 365 nm was used for irradiation for 10 seconds, and the mechanical properties of the prepared composite products were evaluated.
[0064] Moisture content Adhesive composition PMDI surface layer 12% 3% —— Core layer 2.5% —— 4%
[0065] Example 2
[0066] A) Preparation of bonding composition B
[0067] i) Isocyanate component b
[0068] In this embodiment, the isocyanate component is selected from Wanhua Chemical Group CW30 product, CW30 accounts for 65% of the total weight of the adhesive composition, and the photobase generating component selects tetraphenylborate quaternary ammonium salt photobase generating component TJ-PBG-801 (purchased from Shanghai Wujing Chemical), and the added amount is 1.3% of the total weight of the isocyanate component.
[0069] ii) Preparation of polyacrylate copolymer b
[0070] 10.5 g 7-hydroxy-4-methylcoumarin, 7 g 3-bromopropylene and 41.3 g K 2 CO 3 Dissolve in acetone at 45°C, stir for 7 hours at room temperature, cool to room temperature after the reaction is completed, add an appropriate amount of deionized water, separate with a separatory funnel, add 200g of dichloromethane to re-solventize, wash the product with saturated brine, and finally remove the solvent by distillation under reduced pressure to obtain 7-allyloxy-4-methylcoumarin monomer.
[0071] Weigh 80g of methyl methacrylate, 110g of isooctyl acrylate, 10g of divinylbenzene and 2.2g of homemade 7-allyloxy-4-methylcoumarin and emulsify them with 30g of 0.5% sodium dodecyl sulfate aqueous solution; add 300g of 0.2% NaHCO 3 solution, add monomer pre-emulsion and 40g of 2.4% Na 2 S 2 O 8 The aqueous solution was stirred for 4 hours, and after the dropwise addition was completed, the temperature was raised to 85°C and kept for 0.5 hours, and finally cooled to room temperature for discharge.
[0072] B) Pressed wood particle composite products
[0073] Glue was applied to the surface and core wood particle materials according to the addition amount of each component in the table below. After gluing, boards were made with reference to the preparation method of the aforementioned wood particle composite products. UV light with a wavelength of 385 nm was used for irradiation for 15 seconds, and the mechanical properties of the prepared composite products were evaluated.
[0074] Moisture content Adhesive composition PMDI surface layer 12% 4.5% —— Core layer 2.5% —— 6%
[0075] Example 3
[0076] A) Preparation of Adhesive Composition C
[0077] i) Isocyanate component c
[0078] In this embodiment, the isocyanate component is selected from Wanhua Chemical Group 9132FC product, 9132FC accounts for 80% of the total weight of the adhesive composition. The photolatent base component is Irgacure 907 (4-(methylthiobenzoyl)-1-methyl-1-morpholineethane, purchased from Ciba), and the added amount accounts for 2.5% of the isocyanate component.
[0079] ii) Preparation of polyacrylate copolymer c
[0080] 8.5 g of 7-hydroxy-3-carboxycoumarin and 3.6 g of triethylamine were dissolved in 100 ml of dichloromethane, and the mixed solution was gradually dripped into a reaction bottle containing 20.8 g of acryloyl chloride. The reaction bottle was placed in an ice bath, and the reaction was continued for 4 hours after the dripping was completed. Finally, the solvent was distilled off under reduced pressure to obtain acrylic acid-7-(3-carboxycoumarin) ester monomer.
[0081] Weigh 175g of butyl acrylate, 5g of methacrylic acid and 1.2g of homemade 7-(3-carboxycoumarin) acrylate and emulsify them with 200g of 0.5% sodium dodecyl sulfate aqueous solution; add 300g of 0.2% NaHCO 3solution, add monomer pre-emulsion and 60g of 2.4% Na 2 S 2 O 8 The aqueous solution was stirred for 4 hours, and after the dropwise addition was completed, the temperature was raised to 85°C and kept for 0.5 hours, and finally cooled to room temperature for discharge.
[0082] B) Pressed wood particle composite products c
[0083] Glue was applied to the surface and core wood particle materials according to the addition amount of each component in the table below. After gluing, boards were made with reference to the preparation method of the aforementioned wood particle composite products. The boards were irradiated with UV light with a wavelength of 395 nm for 24 seconds, and the mechanical properties of the prepared composite products were evaluated.
[0084] Moisture content Adhesive composition PMDI surface layer 12% 6% —— Core layer 3% 1% 4.5%
[0085] Example 4
[0086] A) Preparation of Adhesive Composition D
[0087] i) Isocyanate component d
[0088] In this embodiment, the isocyanate component is selected from Wanhua Chemical Group PM300E product, PM300E accounts for 90% of the total weight of the adhesive composition. The photobase generating component is 1,1,3,3-tetramethylguanidine tetraphenylboron quaternary ammonium salt (purchased from Kedi Chemical), and the added amount accounts for 3.4% of the content of the isocyanate component.
[0089] ii) Preparation of polyacrylate copolymer d
[0090] 25 g of 7-hydroxy-4-methylcoumarin and 30 g of epichlorohydrin were dissolved in 100 ml of dichloromethane, and the mixed solution was gradually dripped into a reaction bottle containing 20.8 g of acryloyl chloride. The reaction bottle was placed in an ice bath, and the reaction was continued for 4 hours after the dripping was completed. Finally, the solvent was distilled off under reduced pressure to obtain 2-hydroxymethyl-(4-methylcoumarin)oxyethyl-methacrylate monomer.
[0091] Weigh 165g of isooctyl acrylate, 5g of ethylene glycol dimethacrylate, 30g of styrene and 6.7g of homemade 2-hydroxymethyl-(4-methylcoumarin)oxyethyl-methacrylate and emulsify them with 200g of 0.5% sodium dodecyl sulfate aqueous solution; add 300g of 0.2% NaHCO 3 solution, add monomer pre-emulsion and 60g of 2.4% Na 2 S 2 O 8 The solution was stirred for 4 hours, and after the dropwise addition was completed, the temperature was raised to 85°C and kept for 0.5 hour, and finally cooled to room temperature for discharge.
[0092] B) Pressed wood particle composite products
[0093] Glue was applied to the surface and core wood particle materials according to the addition amount of each component in the table below. After gluing, boards were made with reference to the preparation method of the aforementioned wood particle composite products, irradiated with UV for 35 seconds, and the mechanical properties of the prepared composite products were evaluated.
[0094] Moisture content Adhesive composition PMDI surface layer 15% 8% 2% Core layer 2% —— 3%
[0095] Example 5
[0096] ⅰ) Isocyanate component e
[0097] In this embodiment, the isocyanate component is selected from Wanhua Chemical Group CW20 product, CW20 accounts for 70% of the total weight of the adhesive composition. The photobase generating component is selected from 1,1,3,3-tetramethylguanidine tetraphenylboron quaternary ammonium salt (purchased from Kedi Chemical), and the added amount accounts for 4.5% of the content of the isocyanate component.
[0098] ii) Acrylate copolymer
[0099] 21 g of 7-hydroxy-4-methylcoumarin, 6 g of KOH, and 1.1 g of polyethylene glycol were dissolved in 60 ml of deionized water at 40°C. After stirring for 10 min, 16.2 g of chloromethylene styrene was added and reacted for 48 hours. The mixture was cooled and filtered, dissolved in tetrahydrofuran, and washed with methanol. The product was vacuum dried to obtain 7-(4-vinylbenzyloxy)-4-methylcoumarin.
[0100] 130 g butyl acrylate, 50 g styrene, 20 g ethylene glycol dimethacrylate and 9.8 g homemade 7-(4-vinylbenzyloxy)-4-methylcoumarin were weighed and emulsified with 250 g 0.5% sodium dodecyl sulfate aqueous solution. 300 g 0.2% NaHCO was added to the bottom of the reaction flask. 3 solution, add monomer pre-emulsion and 50g mass concentration of 2.4% Na 2 S 2 O 8 The solution was stirred for 4 hours, and after the dropwise addition was completed, 8.95 g of KH550 modified nano-silica was added, and the mixture was kept warm for 1 hour under stirring, and finally cooled to room temperature and discharged.
[0101] A) Pressed wood particle composite products
[0102] Glue was applied to the surface and core wood particle materials according to the addition amount of each component in the table below. After gluing, boards were made with reference to the preparation method of the aforementioned wood particle composite products. The boards were irradiated with a light source with a wavelength of 405 nm for 45 seconds, and the mechanical properties of the prepared composite products were evaluated.
[0103] Moisture content Adhesive composition PMDI surface layer 11% 5.5% —— Core layer 2% 5% 4.6%
[0104] Comparative Example 1
[0105] The photobase generating component in the isocyanate component in Example 1 was replaced with the same amount of dibutyltin disilicate, and the other components, reaction conditions and preparation of the wood composite product remained unchanged.
[0106] Table 1 Comparison of cold pressing adhesion and demoulding properties between the examples and the comparative examples
[0107]
[0108] As can be seen from Table 1, the cold pressing adhesion of all examples is very good before and after storage (0min and 60min), the slab strength is high, and the effect of complete demoulding can be achieved. As can be seen from Example 1 and Comparative Example 1, if the photobase generator is replaced by an organic tin catalyst, although the catalyst can accelerate the curing of isocyanate during hot pressing, the surface NCO is not affected, resulting in sticking of the board, so the catalyst cannot replace the role of the photobase generator.
[0109] Table 2 Mechanical properties of wood particle board after hot pressing of the embodiment and the comparative example
[0110]
[0111] From Table 2, it can be seen that all the examples have good mechanical properties when the contents of PMDI and acrylate copolymer are within the range defined in the claims of the present invention. Suitable photobase concentration and illumination time are key factors in achieving an ideal demoulding effect.
[0112] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
[0113] The present invention discloses an adhesive composition for preparing a wood particle composite product, which can provide a wood particle mixture with sufficient and long-term cold pressing adhesion during cold pressing, ensure that the appearance of the cold pressed slab can be kept intact for a long time, and can achieve a good demoulding effect during hot pressing without using an additional demoulding agent. The present invention discloses a preparation method of the adhesive composition and a preparation method of a wood particle composite product using the adhesive composition, as well as the material performance characteristics and descriptions made in order to make the material meet the application performance and production requirements of the wood particle composite product.
Claims
1. A method for preparing a wood particle board that can be demoulded smoothly, characterized in that: The method comprises the following steps: S1: mixing the binder composition with the wood particle material and paving the mixture into a shape to be pressed, and cold pressing the mixture to obtain a formed slab; S2: irradiating the slab surface with UV light; S3: hot pressing the slab of S2 to obtain a wood particle board; The photobase generating component contained in the adhesive composition described in S1 catalyzes the reaction of NCO groups on the surface of the wood particle board after being irradiated with UV light in S2.
2. The preparation method according to claim 1, characterized in that: S1: The adhesive composition comprises component A and component B, wherein component A comprises polyisocyanate and a photobase generating component, and component B comprises an acrylate polymer; Preferably, the component A accounts for 50-95wt% of the adhesive composition, and the component B accounts for 5-50wt% of the adhesive composition; Preferably, the photobase generating component accounts for 0.1-5 wt % of the A component.
3. The preparation method according to claim 1 or 2, characterized in that: The polyisocyanate in S1 is an aromatic isocyanate, preferably diphenylmethane diisocyanate MDI and / or polymethylene polyphenyl isocyanate PMDI, more preferably PMDI; And / or, the photobase generating component in S1 is one or more of a carbamate compound, a borate compound, a quaternary ammonium salt compound, and a nitrogen heterocyclic amidine compound, preferably a quaternary ammonium salt compound and / or a borate compound.
4. The preparation method according to any one of claims 1 to 3, characterized in that S1 The acrylic ester polymer is obtained by polymerizing two or more monomers selected from C2-C14 (meth) alkyl acrylate, (alkyl) styrene, vinyl alkyl benzene, unsaturated carboxylic acid, alkyl vinyl ester, and polyol (dimethyl) diacrylate; and / or, the acrylic ester polymer described in S1 contains a photosensitive monomer containing a C=C double bond terminated with a coumarin group; Preferably, the photosensitive monomer containing a C=C double bond terminated by a coumarin group is 0.01-2 wt % of the acrylate polymer; And / or, the Tg of the acrylic acid ester copolymer described in S1 is -40°C to 20°C, preferably -20°C to 10°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: S1 The amount of the binder composition added is not less than 2% of the total weight of the wood particle material.
6. The preparation method according to any one of claims 1 to 5, characterized in that: S2: the wavelength of UV light irradiating the surface of the slab is 200-650nm, preferably 300-400nm; And / or, S2 lighting time 5-60s.
7. A binder composition for preparing a wood particle board, wherein the composition is the binder composition used in the method for preparing a wood particle board according to any one of claims 1 to 6.
8. Use of a method for preparing a wood particle board that can be demoulded smoothly, the method being the method according to any one of claims 1 to 6, and being used for preparing man-made panels, preferably for preparing oriented strand board, oriented laminated lumber, and fiberboard.
Citation Information
Patent Citations
Photocurable pressure-sensitive adhesive composition
CN101679829A
Nano stamping photoresist surface modifier
CN102604454A
Cold-pressed mats of lignocellulosic material having improved cold tack and a process for their production
CN103153563A
Special adhesive for straw man-made board and preparation of straw man-made board
CN104293274A
Reaction type polyurethane hot melt adhesive with multiple curing modes and preparation method of reaction type polyurethane hot melt adhesive
CN112724915A
